37 Multiplexed measurement of candidate protein biomarkers of cardiovascular disease in blood. (16th October 2019) - Tonry, C; McDonald, K; Ledwidge, M; Hernandez, B; Glezeva, N; Rooney, C; Morrissey, B; Pennington, SR; Baugh, JA; Watson, CJ
Abstract : Not available for publication.